2018
DOI: 10.2105/ajph.2018.304529
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis and Current Health Disparities in California: Making the Invisible Visible

Abstract: Tuberculosis (TB) continues to have devastating consequences for patients both globally and locally, with disease risk concentrated in specific subgroups defined by race, ethnicity, and nativity. We highlight TB disparities in California in 2016, and describe opportunities to reduce disparities by scaling up screening and treatment of latent TB infection (LTBI) in primary care settings. Primary impediments to mainstreaming LTBI screening and treatment and reducing TB disparities include poor understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is well described that transportation costs contribute globally to the financial burden placed on patients with TB. 4 There is an association for patients who are non-English speaking or of racial and ethnic minorities to have less access to personal transportation 23 , 24 ; public transportation in our patient population would require at least a 2 transfer route to move from community to RISE Clinic 25 —an investment not only in cost but even more critically in time taken from other life tasks such as work or child care. Twenty-five percent of identified patients with LTBI in our study were uninsured; it is unknown, but likely this contributed to losses in the care cascade—either in obtaining a CXR, transportation costs, or unclear understanding that TB services are free at RISE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well described that transportation costs contribute globally to the financial burden placed on patients with TB. 4 There is an association for patients who are non-English speaking or of racial and ethnic minorities to have less access to personal transportation 23 , 24 ; public transportation in our patient population would require at least a 2 transfer route to move from community to RISE Clinic 25 —an investment not only in cost but even more critically in time taken from other life tasks such as work or child care. Twenty-five percent of identified patients with LTBI in our study were uninsured; it is unknown, but likely this contributed to losses in the care cascade—either in obtaining a CXR, transportation costs, or unclear understanding that TB services are free at RISE.…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic minorities—who are disproportionately at higher risk for LTBI—are more likely to be uninsured in the United States, highlighting structural discrimination that impacts access to LTBI care. 5 , 24 , 28 - 30 Although the World Health Organization states that achieving Universal Health Coverage is a key target for nations to achieve the sustainable development goals, US dialog around the Affordable Care Act and extension of its reach to cover the uninsured has slowed progress toward increasing patient access to care such as that for LTBI. The goal of Zero Catastrophic costs placed forward by the WHO End TB could include mitigation strategies for health inequities by engaging primary care providers already in the community of patients to decrease cost related to untreated LTBI progressing to TB disease that requires specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…In California, half of individuals diagnosed with TB are hospitalized and 10% of individuals with TB disease do not survive TB treatment [ 3 , 4 ]. TB is both a health equity issue and a preventable and costly burden on the healthcare system [ 5 , 6 ]. Cost effectiveness studies show that TB interventions focused on non-U.S.-born (USB) individuals in California could avert 9800 TB cases and $179 million treatments costs over 29 years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common risk factor in the US for TB is having been non-US born; this population already faces many barriers to accessing health care [4]. As stated by Katrak and Flood in a 2018 commentary, it is believed that knowledge gaps among primary care providers (PCPs) and lack of familiarity with LTBI treatment regimens (recommended regimens in the US include 9 months of isoniazid, 4 months of rifampin, 3 months of weekly rifapentine and isoniazid) remain significant barriers to treatment for underserved populations [5]. Furthermore, non-US born populations such as refugees and asylum seekers can experience difficulty in connecting with other services, and it has been suggested that this can be worsened both by poor communication among providers as well as complex healthcare systems [6].…”
Section: Introductionmentioning
confidence: 99%